Evaluating Policies to Implement the Paris Agreement: A Toolkit with Application to China - Ian Parry; Baoping Shang; Nate Vernon; Philippe Wingender (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper describes a model, implemented in an Excel spreadsheet, for evaluating a wide range of fiscal and regulatory instruments policymakers might consider for implementing their Paris mitigation pledges. Policies are evaluated against a range of metrics, including impacts on carbon dioxide (CO2) emissions, revenue, deaths from local air pollution, economic welfare benefits and costs, and incidence across household and industry groups. The model is applied to China, the world's largest emitter, but could be readily transferred to most other countries.
Keywords: Q48; Q54; Q58; H23; 330; Paris Agreement; carbon tax; China; air pollution; coal tax; emissions trading; incidence; welfare effects; spreadsheet model